MXene-based ultrafast charging positive electrode and preparation method and application thereof

By mixing MXene with the positive electrode material in deionized water, a high-conductivity positive electrode slurry is prepared, which solves the problem of insufficient conductivity of the positive electrode of the lithium-ion battery, and achieves the effect of ultrafast charging and safety improvement.

CN119400811APending Publication Date: 2025-02-07XUZHOU LANOXENE INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411392371.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The conductivity of the positive electrode material of the existing lithium-ion battery is insufficient, resulting in insufficient battery reaction during charging, low actual capacity, and safety hazards of thermal runaway.

Method used

Using MXene as the conductive agent, a high-conductive positive electrode slurry was prepared by mixing it with the positive electrode material, a thickener and an aqueous binder in deionized water, and an ultra-fast charging positive electrode was obtained by vacuum drying.

Benefits of technology

The preparation of a highly conductive positive electrode is achieved, and the charging and discharging performance of lithium-ion batteries is improved, especially at large-scale ultra-fast charging, and the process is environmentally friendly and pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400811A_ABST
    Figure CN119400811A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium ion batteries, and discloses an MXene-based ultrafast charge positive electrode and a preparation method and application thereof, and the method comprises the following steps: dispersing an MXene material and a positive electrode material in deionized water, adding a thickening agent and a water-based binder, and uniformly mixing to obtain positive electrode slurry; and coating an aluminum foil with the positive electrode slurry, and carrying out vacuum drying to obtain the positive plate. The pulping process of the positive plate is simple to operate and concise, and the existing production process can be directly replaced under the condition of not changing other conditions; the slurry has good dispersity and good consistency before and after the slurry, and the prepared positive electrode has an excellent point-to-surface conductive network and has excellent charge-discharge performance under high rate; after a battery is assembled by the positive plate, charging and discharging under ultra-large current can be realized, ultra-fast charging under 20C multiplying power can be realized, and a thought is provided for constructing a novel, environment-friendly and high-power lithium ion battery of the next generation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a MXene-based ultrafast charging positive electrode and a preparation method and application thereof. Background Art

[0002] With the increasing popularity of new energy vehicles, battery life anxiety and safety hazards have become hot issues that people are increasingly concerned about. Among them, the main reason for battery life anxiety is that the actual capacity is low due to the insufficient battery reaction of the positive electrode material during the charging process of the lithium-ion battery; and the safety hazard is mainly caused by thermal runaway of the lithium-ion battery during the charging process. The above two problems are mainly attributed to the poor conductivity of the positive electrode material. Conventional conductive agents, such as acetylene black, Ketjen black, carbon nanotubes, etc., have average conductivity and cannot meet the requirements of constructing a high-conductivity positive electrode.

[0003] MXene is a new type of two-dimensional material. Its excellent conductivity (8000S / cm) makes it a new type of conductive agent. However, MXene has OH groups at the end of its surface. - This property makes MXene unable to be used as a conductive additive in commercial NMP organic solvent-based positive electrodes (LiFePO4, ternary NCM materials, Li4Ti5O 12 ) coating process. Therefore, how to develop a new cathode slurry process with MXene as a conductive agent is the key to promoting the industrialization of ultrafast charging batteries. Summary of the invention

[0004] The purpose of the present invention is to provide a novel slurrying process for ultrafast charging positive electrodes and its application, so as to solve the problem of using MXene as a conductive agent in the positive electrode field and constructing ultrafast charging positive electrodes.

[0005] To achieve the above objectives, on the one hand, the present invention provides a method for preparing an ultrafast charging positive electrode based on MXene, which comprises the following steps:

[0006] S1. Disperse MXene material and positive electrode material in deionized water, add thickener and aqueous binder and mix well to obtain positive electrode slurry. The proportion of each component of the positive electrode slurry is as follows: deionized water 88%-92wt%, positive electrode material 5%-10wt%, MXene 0.1-1wt%, thickener 0.1-1wt%, aqueous binder 0.1-1wt%; the positive electrode material is LiFePO4, Li4Ti5O 12, ternary NCM523, ternary NCM811, ternary NCM111; the thickener is at least one of starch, gum arabic, pectin, gelatin, sodium carboxymethyl cellulose; the aqueous binder is at least one of polyvinyl alcohol, styrene-butadiene rubber, LA132, guar gum, chitosan;

[0007] S2. Coat the positive electrode slurry on aluminum foil and vacuum dry it to obtain a positive electrode sheet.

[0008] As a further preferred technical solution of the present invention, the MXene material includes at least one of Ti3C2, MoC2, V2C, Nb2C, TiC2, (Mo2Sc)C2, (Mo2Ti)C2, Ti4N3, V4C3, Nb4C3, and Ta4C3.

[0009] As a further preferred technical solution of the present invention, step S1 specifically includes:

[0010] First, MXene material and cathode material are dispersed uniformly in deionized water by ultrasonication to obtain a mixed solution A;

[0011] Then, a thickener is added to the mixed solution A, and the mixed solution A is dispersed evenly by ultrasonic vibration to obtain a mixed solution B;

[0012] Finally, an aqueous binder is added to the mixed solution B and stirred evenly in a stirrer to obtain a positive electrode slurry.

[0013] 4. The MXene-based ultrafast charging positive electrode according to claim 3, characterized in that the frequency of the agitator is 300-800r / min.

[0014] As a further preferred technical solution of the present invention, in step S2, the coating thickness of the positive electrode slurry is 10-100 μm.

[0015] As a further preferred technical solution of the present invention, in step S2, the vacuum drying temperature is 90-100°C and the time is 6-14h.

[0016] According to another aspect of the present invention, the present invention also provides an ultrafast charging positive electrode, which is prepared by the above method.

[0017] According to another aspect of the present invention, the present invention also provides an application of an ultra-fast charging positive electrode as a positive electrode of a lithium-ion battery.

[0018] Compared with the prior art solutions, the present invention has the following advantages:

[0019] (1) The positive electrode slurry making process of the present invention is simple to operate and has a concise process, and can directly replace the existing production process without changing other conditions.

[0020] (2) The pulping method of the present invention can directly replace the current positive electrode pulping process to achieve large-scale coating.

[0021] (3) The present invention uses an aqueous binder, and the drying process in a vacuum oven can significantly remove the OH adsorbed on the positive electrode. - , effectively avoiding the OH in the water-based binder - The optimal temperature for the positive electrode is 100°C.

[0022] (4) The positive electrode slurrying process of the present invention is green, environmentally friendly and pollution-free. Deionized water is used instead of N-methylpyrrolidone (NMP) as a solvent, which overcomes the problem of NMP having slight toxicity in the manufacturing process of traditional lithium-ion positive electrode slurry and perfectly solves the safety problem in the process.

[0023] (5) The slurry preparation process of the positive electrode involved in the present invention has good dispersibility of the slurry and good consistency before and after the slurry. The prepared positive electrode has an excellent point-to-surface conductive network and excellent charge and discharge performance at a high rate.

[0024] (6) The positive electrode pulping process involved in the present invention can realize charging and discharging under ultra-large current after assembling the battery, and realize ultra-fast charging (within 3 minutes) at a rate of 20C, providing ideas for building the next generation of new, environmentally friendly, high-power lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0026] Figure 1 This is the SEM photograph of the traditional positive electrode obtained in Comparative Example 1.

[0027] Figure 2 This is a SEM photograph of the positive electrode obtained in Example 1.

[0028] Figure 3 This is a comparison chart of the conductivity of the positive electrode obtained in Comparative Example 1 and Example 1.

[0029] Figure 4 The graphs are the cycle curves of the positive electrodes obtained in Comparative Example 1 and Example 1 respectively assembled into full batteries at a rate of 20C.

[0030] Figure 5 The conductivity comparison diagram of the positive electrode obtained in Comparative Example 2 and Example 2 is shown.

[0031] Figure 6 The first-week charge-discharge curves of the positive electrodes obtained in Comparative Example 2 and Example 2 at a rate of 20C are shown.

[0032] Figure 7 This is a comparison chart of the conductivity of the positive electrode obtained in Comparative Example 3 and Example 3.

[0033] Figure 8 The first week charge and discharge curves of the positive electrodes obtained in comparative example 3 and embodiment 3 at a rate of 20C.

[0034] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION

[0035] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0036] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0037] Comparative Example 1:

[0038] 90 mg of LiFePO4, 8 mg of acetylene black, and 2 mg of PVDF were added in an agate mortar, and NMP was added as a solvent, and the above substances were uniformly mixed to prepare a positive electrode slurry.

[0039] The positive electrode slurry was evenly coated on aluminum foil by blade coating with a coating thickness of 20 μm, and then dried in a vacuum oven at 60°C for 12 hours to ensure that the solvent was completely removed. The obtained positive electrode sheet was cut into a circular positive electrode sheet with a diameter of 8 mm to serve as the positive electrode of a lithium-ion battery. The prepared positive electrode sheet was immersed in an electrolyte of 1.0M LiPF6 in EC:DMC:EMC=1:1:1Vol%, with lithium foil as the positive electrode and Celgard 2300 as the separator, and the CR-2032 coin battery was assembled in a glove box to complete the half-cell assembly.

[0040] Embodiment 1:

[0041] A method for applying MXene as a conductive additive to a positive electrode of a lithium-ion battery comprises the following steps:

[0042] 8 mg of MXene material was ultrasonically dispersed in 1 ml of deionized water to obtain a uniformly mixed black MXene dispersion, and then 90 mg of LiFePO4 was added to the prepared dispersion and ultrasonicated. Then 1 mg of pectin was added and dispersed by shaking, and then 1 mg of polyvinyl alcohol was added and stirred continuously at a frequency of 500 r / min to finally obtain a viscous and uniform lithium ion aqueous positive electrode slurry.

[0043] The positive electrode slurry was evenly coated on the aluminum foil by blade coating, with a coating thickness of 20 μm, and then dried in a vacuum oven at 100 ° C for 12 hours to ensure that the solvent was completely removed. The obtained positive electrode sheet was cut into a circular positive electrode sheet with a diameter of 8 mm to serve as the positive electrode of the lithium-ion battery. The prepared positive electrode sheet was immersed in 1.0M LiPF6 in EC:DMC:EMC=1:1:1Vol% electrolyte, with lithium foil as the positive electrode and Celgard 2300 as the separator, and the CR-2032 coin battery was assembled in the glove box to complete the half-cell assembly.

[0044] The half-cells assembled in the above-mentioned embodiment 1 and comparative example 1 were subjected to comparative tests, as follows:

[0045] See attached Figure 1 and 2 , respectively, are SEM photos of the positive electrode sheets obtained in Comparative Example 1 and Example 1. It can be seen that the positive electrode constructed by the conventional process in Comparative Example 1 exhibits large voids and uneven distribution of LiFePO4, while the positive electrode constructed in Example 1 uses a water-based thickener and binder, making the LiFePO4 positive electrode more compact.

[0046] See attached Figure 3 , which is a comparison chart of the conductivity of the positive electrode obtained in Example 1 and Comparative Example 1. It can be seen that the conductivity of Example 1 is much higher than that of Comparative Example 1. The reason for the high conductivity can be attributed to the better conductivity of the positive electrode prepared in Example 1. The conductive network between the conductive agent and the active material is directly related to the conductivity. The more developed the conductive network, the better the conductivity. The two-dimensional nanosheets of MXene can wrap the LiFePO4 particles well, and the contact between the two is face-to-face point contact. The conductive network formed by this contact mode is more developed, so this is conducive to further improving its ultra-fast charging electrochemical performance.

[0047] See attached Figure 4 , which are the cycle curves of the positive electrodes obtained in Example 1 and Comparative Example 1 respectively assembled into full batteries at a rate of 20C. As shown in the figure, Example 1 is a positive electrode prepared by the pulping process based on the ultra-fast charging positive electrode, which exhibits excellent electrochemical performance. The performance at high rate is much higher than that of the positive electrode obtained in Comparative Example 1, and the discharge specific capacity at a rate of 20C is 115mAh g -1, which can achieve super fast charging. This excellent performance can be attributed to the conductive network constructed by the positive electrode of Example 1. The two-dimensional nanosheets of MXene can wrap the LiFePO4 particles well, forming a surface-point contact with LiFePO4. The conductive network formed by this contact mode is more developed, and the transmission of electrons and ions provides more conductive sites, so that electrons and ions can migrate faster, so stable fast charging is achieved at a rate of 20C.

[0048] Comparative Example 2:

[0049] In an agate mortar, 90 mg of NCM523, 8 mg of acetylene black, and 2 mg of PVDF were added with NMP as a solvent, and the above substances were uniformly mixed to prepare a positive electrode slurry.

[0050] The positive electrode slurry was evenly coated on the aluminum foil by scraping, with a coating thickness of 20 μm. Then it was dried in a vacuum oven at 60 ° C for 12 hours to ensure that the solvent was completely removed, and the obtained positive electrode sheet was cut into a circular positive electrode sheet with a diameter of 8 mm as the positive electrode of the lithium-ion battery. The prepared positive electrode sheet was immersed in 1.0M LiPF6 in EC:DMC:EMC=1:1:1Vol% electrolyte, with lithium foil as the positive electrode and Celgard 2300 as the separator, and the CR-2032 coin battery was assembled in the glove box to complete the half-cell assembly.

[0051] Embodiment 2:

[0052] A method for applying MXene as a conductive additive to a positive electrode of a lithium-ion battery comprises the following steps:

[0053] 8 mg of MXene material was ultrasonically dispersed in 1 ml of deionized water to obtain a uniformly mixed black MXene dispersion, and then 90 mg of NCM523 was added to the prepared dispersion and ultrasonicated. Then 1 mg of pectin was added and dispersed by shaking, and then 1 mg of polyvinyl alcohol was added and stirred continuously at a frequency of 500 r / min to finally obtain a viscous and uniform lithium ion aqueous positive electrode slurry.

[0054] The positive electrode slurry was evenly coated on the aluminum foil by blade coating, with a coating thickness of 20 μm, and then dried in a vacuum oven at 100 ° C for 12 hours to ensure that the solvent was completely removed. The obtained positive electrode sheet was cut into a circular positive electrode sheet with a diameter of 8 mm to serve as the positive electrode of the lithium-ion battery. The prepared positive electrode sheet was immersed in 1.0M LiPF6 in EC:DMC:EMC=1:1:1Vol% electrolyte, with lithium foil as the positive electrode and Celgard 2300 as the separator, and the CR-2032 coin battery was assembled in the glove box to complete the half-cell assembly.

[0055] The half-cells assembled in the above-mentioned embodiment 2 and comparative example 2 were subjected to comparative tests, as follows:

[0056] See attached Figure 5 , which is a comparison chart of the conductivity of the positive electrode obtained in Example 2 and Comparative Example 2. It can be seen that the conductivity of Example 2 is much higher than that of Comparative Example 2. The reason for the high conductivity can be attributed to the better conductivity of the positive electrode prepared in Example 2. The conductive network between the conductive agent and the active material is directly related to the conductivity. The more developed the conductive network, the better the conductivity. The two-dimensional nanosheets of MXene can wrap the NCM523 particles well, and the contact between the two is face-to-face point contact. The conductive network formed by this contact mode is more developed, so this is conducive to further improving its ultra-fast charging electrochemical performance.

[0057] See attached Figure 6 , is the first week charge and discharge curve diagram of Example 2 and Comparative Example 2. At a rate of 20C, the discharge specific capacity of Example 2 is significantly higher than that of Comparative Example 2, indicating that Example 2 has better electrochemical performance at a high rate. This excellent performance can be attributed to the conductive network constructed by the positive electrode of Example 2, which forms a surface-point contact with the NCM523 material, providing more conductive sites for the transmission of electrons and ions, thereby greatly improving the conductivity.

[0058] Comparative Example 3:

[0059] 90 mg Li4Ti5O was added in an agate mortar. 12 , 8 mg acetylene black, 2 mg PVDF, and NMP as a solvent, and the above substances are evenly mixed to prepare a positive electrode slurry.

[0060] The positive electrode slurry was evenly coated on the aluminum foil by scraping, with a coating thickness of 20 μm. Then it was dried in a vacuum oven at 60 ° C for 12 hours to ensure that the solvent was completely removed, and the obtained positive electrode sheet was cut into a circular positive electrode sheet with a diameter of 8 mm as the positive electrode of the lithium-ion battery. The prepared positive electrode sheet was immersed in 1.0M LiPF6 in EC:DMC:EMC=1:1:1Vol% electrolyte, with lithium foil as the positive electrode and Celgard 2300 as the separator, and the CR-2032 coin battery was assembled in the glove box to complete the half-cell assembly.

[0061] Embodiment three:

[0062] A method for applying MXene as a conductive additive to a positive electrode of a lithium-ion battery comprises the following steps:

[0063] 8 mg of MXene material was ultrasonically dispersed in 1 ml of deionized water to obtain a uniformly mixed black MXene dispersion. Then 90 mg of Li4Ti5O 12 Add to the prepared dispersion and continue ultrasonication. Then add 1 mg of pectin, shake and disperse, then add 1 mg of polyvinyl alcohol, and continue stirring at a frequency of 500 r / min to finally obtain a viscous and uniform lithium ion aqueous positive electrode slurry.

[0064] The positive electrode slurry was evenly coated on the aluminum foil by blade coating with a coating thickness of 20 μm. It was then dried in a vacuum oven at 100 ° C for 12 hours to ensure that the solvent was completely removed. The obtained positive electrode sheet was then cut into a circular positive electrode sheet with a diameter of 8 mm to serve as the positive electrode of a lithium-ion battery. The prepared positive electrode sheet was immersed in 1.0M LiPF6 in EC:DMC:EMC=1:1:1Vol% electrolyte, with lithium foil as the positive electrode and Celgard 2300 as the separator, and the CR-2032 coin battery was assembled in a glove box to complete the half-cell assembly.

[0065] The half-cells assembled in the above-mentioned embodiment 3 and comparative example 3 were subjected to comparative tests, as follows:

[0066] See attached Figure 7 , which is a comparison chart of the conductivity of the positive electrode obtained in Example 3 and Comparative Example 3. It can be seen that the conductivity of Example 3 is much higher than that of Comparative Example 3. The reason for the high conductivity can be attributed to the better conductivity of the positive electrode prepared in Example 3. The conductive network between the conductive agent and the active material is directly related to the conductivity. The more developed the conductive network, the better the conductivity. The two-dimensional nanosheets of MXene can convert Li4Ti5O 12 The particles are well wrapped, and the contact between the two is face-to-point contact. The conductive network formed by this contact mode is more developed, so it is beneficial to further improve its ultra-fast charging electrochemical performance.

[0067] See attached Figure 8 The first-week charge-discharge curves of Example 3 and Comparative Example 3 are shown in the figure. As shown in the figure, at a rate of 20C, the discharge specific capacity of Example 3 is higher than that of Comparative Example 3, indicating that Example 3 has better electrochemical performance at a high rate. This excellent performance can be attributed to the conductive network constructed by the positive electrode of Example 3, which is similar to Li4Ti5O 12 Surface-point contact is formed, providing more conductive sites for the transmission of electrons and ions, thereby greatly improving conductivity.

[0068] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.

Claims

1. A method for preparing an ultrafast charging positive electrode based on MXene, characterized in that: The following steps are involved: S1. Disperse MXene material and cathode material in deionized water, add thickener and aqueous binder and mix well to obtain cathode slurry, wherein the proportion of each component of the cathode slurry is: deionized water 88%-92wt%, cathode material 5%-10wt%, MXene 0.1-1wt%, thickener 0.1-1wt%, aqueous binder 0.1-1wt%; The positive electrode material is LiFePO4, Li4Ti5O 12 , at least one of ternary NCM523, ternary NCM811, and ternary NCM111; The thickener is at least one of starch, gum arabic, pectin, gelatin and sodium carboxymethyl cellulose; The aqueous binder is at least one of polyvinyl alcohol, styrene-butadiene rubber, LA132, guar gum, and chitosan; S2. Coat the positive electrode slurry on aluminum foil and vacuum dry it to obtain a positive electrode sheet.

2. The method for preparing a superfast charging positive electrode based on MXene according to claim 1, characterized in that: The MXene material includes at least one of Ti3C2, MoC2, V2C, Nb2C, TiC2, (Mo2Sc)C2, (Mo2Ti)C2, Ti4N3, V4C3, Nb4C3, and Ta4C3.

3. The method for preparing a superfast charging positive electrode based on MXene according to claim 1, characterized in that: Step S1 specifically includes: First, MXene material and cathode material are dispersed uniformly in deionized water by ultrasonication to obtain a mixed solution A; Then, a thickener is added to the mixed solution A, and the mixed solution A is dispersed evenly by ultrasonic vibration to obtain a mixed solution B; Finally, an aqueous binder is added to the mixed solution B and stirred evenly in a stirrer to obtain a positive electrode slurry.

4. The method for preparing a superfast charging positive electrode based on MXene according to claim 3, characterized in that: The frequency of the stirrer is 300-800r / min.

5. The method for preparing a superfast charging positive electrode based on MXene according to claim 1, characterized in that: In step S2, the coating thickness of the positive electrode slurry is 10-100 μm.

6. The method for preparing a superfast charging positive electrode based on MXene according to claim 1, characterized in that: In step S2, the vacuum drying temperature is 90-100°C and the time is 6-14h.

7. An ultra-fast charging positive electrode, characterized in that: The method is prepared by any one of claims 1 to 6.

8. Use of the ultrafast charging positive electrode according to claim 7 as a positive electrode of a lithium-ion battery.